Pharmacokinetics of chloramphenicol (CAP) in gilthead sea bream (Sparus aurata) and its in vitro activities against important bacterial fish pathogens - TYRPENOU (Α.Ε. ΤΥΡΠΕΝΟΥ), A. E.; RIGOS (Γ. ΡΗΓΟΣ), G.; YAGNISI (Μ. ΓΙΑΓΝΙΣΗ), M.; NENGAS (Ι. ΝΕΓΚΑΣ), I.; ALEXIS (Μ. ΑΛΕΞΗΣ), M. (Journal of the Hellenic Veterinary Medical Society, 2017)
The pharmacokinetics of chloramphenicol (CAP) in gilthead sea bream (Sparus aurata), a warm water farmed fish species and its in vitro efficacy against important bacterial diseases of Mediterranean mariculture were investigated in this study. After an intravascular injection (10 mg/kg/fish), the distribution half-life (tl/2a) and the elimination half-life (tl/2ß) of CAP were calculated to be 1.6 and 69 h, respectively. Tissue penetration of CAP was found to be moderate since both the apparent volume of distribution of the drug at steady-state (V<i(ss)) and the apparent volume of the central compartment (Vc) were calculated to be 1.13 and 0.90 L/kg. The total clearance (CLp) of the drug was slow (0.022 L/kg/h). The minimum inhibitory concentration (MIC) values of CAP in distilled water supplemented with 2% NaCl against Vibrio anguillarum serotype lb, Photobacterium damsela subsp. piscicida, V alginolyticus and V ßuvialis were determined to be 4.78 pg/mL, while it was 0.60 pg/mL for V. damsela. The addition of 10 mM Ca2+ and 55 mM Mg2+ in the medium revealed MIC values of 19.13 pg/mL for V alginolyticus and V ßuvialis, whereas showed no effect for V anguillarum P. damsela subsp. Piscicida and V damsela. The results indicate that CAP displayed a satisfactory kinetic profile and it is eliminated fast from gilthead sea bream muscle; however, its high MIC values stress show a possible inefficacy against important bacterial pathogens of Mediterranean mariculture.